2018
DOI: 10.1002/cam4.1381
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic changes in plasma Epstein–Barr virus DNA load during treatment have prognostic value in nasopharyngeal carcinoma: a retrospective study

Abstract: Circulating plasma Epstein–Barr virus DNA (EBV DNA) is related to tumor recurrence and metastasis and has potential as a dynamic, sensitive, and specific marker in nasopharyngeal carcinoma (NPC). We investigated the clinical significance of assessing plasma EBV DNA load at various time points during treatment. Patients with NPC (n = 949) for whom plasma EBV DNA load was measured by real‐time quantitative polymerase chain reaction (RT‐qPCR) before treatment (pre‐EBV) and at midtreatment (mid‐EBV), end of treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
3
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 20 publications
2
24
3
6
Order By: Relevance
“…Based on this dynamic change, we divided 252 patients into 5 subgroups/patterns and performed survival analysis. This was different from the previous reports [20][21][22][23][24][25][26], which mainly focused on the following time points primarily from pre-treatment to 3 months post-treatment.…”
Section: Discussioncontrasting
confidence: 84%
See 2 more Smart Citations
“…Based on this dynamic change, we divided 252 patients into 5 subgroups/patterns and performed survival analysis. This was different from the previous reports [20][21][22][23][24][25][26], which mainly focused on the following time points primarily from pre-treatment to 3 months post-treatment.…”
Section: Discussioncontrasting
confidence: 84%
“…Many studies have reported that plasma EBV DNA loads and its dynamic changes could be used as a predictive marker for NPC prognosis at limited time points [20][21][22][23][24][25][26], such as pre-treatment and 3 months post-treatment, however, the prognostic value and dynamic changes of plasma EBV DNA at other time points, such as more than 3 months post-treatment, are not be fully understood yet. Notably, in this study, we enrolled 252 NPC patients who received plasma EBV DNA tests at 4 time points (pre-treatment, 3, 12, and 24 months post-treatment).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study by He et al, detectable EBV DNA at the end of treatment was also associated with significantly poorer OS, DMFS, and progression-free survival (PFS). Among patients with detectable EBV DNA at the end of treatment, adjuvant therapy significantly improved OS (P = 0.03) and DMFS (P = 0.04) [36]. Adjuvant therapy might bring survival benefit to these patients with positive plasma EBV DNA at the end of RT, but it needs to be confirmed by prospective clinical trials.…”
Section: Discussionmentioning
confidence: 96%
“…We have previously reported the potential bene ts of adjuvant treatment for patients with detectable Epstein Barr virus DNA (EBV DNA) load at the end of treatment [10] in addition to the prognostic value of EBV DNA concentrations during treatment [11]. Tumor response and patient survival can also be predicted based on the clearance rates of plasma EBV DNA during the rst month of chemotherapy.…”
Section: Introductionmentioning
confidence: 99%